P207 COVID-19: a prevalence rate two times lower than that of the general population in French patients with Inflammatory Bowel Disease treated with intravenous biologic agents. (21st January 2022) - Lelong, M; Nancey, S; Bouguen, G; Allez, M; Serrero, M; Chupin, A; Caillo, L; Viennot, S; Blanc, P; Reimund, J M; Laharie, D; Olivier, R; et al.
Abstract: Background: Patients with Inflammatory Bowel Disease (IBD), either Crohn's Disease (CD) or Ulcerative Colitis (UC), treated with immunosuppressants and/or biotherapy might have an altered immune response to SARS-CoV-2 infection. The aim of this study was to evaluate the incidence of COVID-19 in a French cohort of IBD patients treated with infliximab or vedolizumab during the first epidemic wave and to identify factors associated with the risk of infection. Methods: All patients with IBD treated with infliximab or vedolizumab from March to June 2020 in 16 French centres were included and followed for 6 months. At baseline, clinical, demographic, family and socio-professional data were collected. At each of their day hospitalization, patients reported the occurrence of symptoms of COVID-19, and the performance of a diagnostic test, if so. Serum was collected at each visit to detect immunisation by SARS-CoV-2 at the end of follow-up and to measure trough levels. Peripheral blood lymphocytes (PBLs) were frozen at each visit for 50% of patients to further analyse the immunological changes associated with COVID-19. Results: 1079 patients were included (CD n=690, mean age 41.6 years, mean disease duration 13.3 years). Clinical and demographic data at baseline are detailed in Tables 1 and 2, respectively. 143 patients (13.3%) had one or more co-morbidities associated with a risk of severe COVID-19 (hypertension 5.6%, chronic lung disease 5%, diabetes 2.4%, obesity 0.3%). Over the 6 months of follow-up, 458 patients (42%) had active disease defined by an HBI score >4 or Mayo score >2 and/or treatment optimisation (dose increase, shortening of infusion interval, addition of an immunosuppressant or change of biotherapy). 111 patients (10.2%) received corticosteroids at least occasionally (self-medication was not excluded). 341 patients (32%) were tested for COVID-19 by nasal swab, of whom 23 were positive. Three patients were hospitalized. Regarding serology, in the first 13 centres analysed hitherto (886 patients), 20 patients were seropositive at the end of follow-up before the start of the vaccination campaign (January 2021), i.e. 2.2%, compared to 4.5% in the general population at the same period according to Santé Publique France data. Conclusion: The preliminary analysis of this French cohort confirms that patients with IBD are not at higher risk of severe COVID-19 despite the use of biotherapy and repeated hospital stays. This population was significantly less infected than the general population. Clinical, demographic and immunological factors associated with SARS-CoV-2 infection are being analysed as well as factors associated with a lower incidence of infection compared to the general population.